Possible effects of climate change on the early development of pea, broad bean, maize and sunflower in Mediterranean region - Andrade, José (2013)
Temperature, water and light affect directly crop growth and development. Extremes variations of temperature near the surface of bare soils and quick changes of soil water content due to irregular rainfall and high evaporative demand affect markedly crop productivity in Mediterranean areas. At these conditions, crop productivity depends strongly on its early development. Both changes on net radiation at soil-atmosphere interface and on annual course of rainfall affect directly parameters of soil thermal regimes and soil water availability and, therefore, the early development of crops. According to IPCC Fourth Assesment report, climate change in Southern Europe “is projected to worsen hygrometric and thermal conditions (high temperature and drought) and to reduce water availability” and, consequently, to decrease general crop productivity. The aim of this study is to evaluate the thermal and hydric conditions at soil top layer under different scenarios concerning to of climate changes and, consequently, their effects on the early development of some representative crops of Mediterranean agriculture (pea, broad bean, maize and sunflower). These effects were discussed based on thermal time concept. For this purpose, temperatures at usual sowing times of winter crops (October) and summer crops (April) were recorded in the top layer of a Luvisol and a Vertisol and compared to those recorded in the air above ground. In addition, speed, size and dispersion of germination, emergence and leaf production were simulated from values of bioclimatic parameters (cardinal temperatures and thermal times referred to different phases of establishment) found in the literature. In both sowing times, monthly mean temperatures at soil top layer were significantly greater (*P<0.05) than those found in the air above ground. However, relationship between air and top soil temperatures was different either in the two soils or in two months. Summer crops seem to be less affected by an increase in temperature than winter crops. Otherwise, the former seem to be more affected by decrease in soil water availability than the later. In addition, final emergence and speed of emergence and leaf production of different species will be more affected by global warming than dispersion around of most likely thermal times. The magnitude of these effects depends also on the magnitude of warming.